POME treatment utilizing high rate hybrid anaerobic reactor - Megat Mohd Noor, Megat Johari; Jusoh, Ahmad; Ghazali, Abdul Halim (1989)
A study was conducted on the performance of a 50 litres upflow hybrid anaerobic digester in treating Palm Oil Mill Effluent (POME) which is noted for its high strength nature. The bacterial growth film on the PVC rings in the digester enables the reduction of the hydraulic retention times and the elimination of the sludge recycling process. The digester was operated at an average temperature of 30°C with an average COD loading rate of 5.2 kg/m3/d. The digester reduces about 40 of TS, 62% of COD, 70% of VS as well as 90% and 95% of VSS and SS respectively. The SS reduction in the hybrid digester is the highest compared to a few other treatment techniques